2006
DOI: 10.3168/jds.s0022-0302(06)72065-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trisodium Citrate Concentration and Cooking Time on the Physicochemical Properties of Pasteurized Process Cheese

Abstract: The effects of the concentration of trisodium citrate (TSC) emulsifying salt (0.25 to 2.75%) and holding time (0 to 20 min) on the textural, rheological, and microstructural properties of pasteurized process Cheddar cheese were studied using a central composite rotatable design. The loss tangent parameter (from small amplitude oscillatory rheology), extent of flow (derived from the University of Wisconsin Meltprofiler), and melt area (from the Schreiber test) all indicated that the meltability of process chees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
90
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(113 citation statements)
references
References 28 publications
15
90
3
Order By: Relevance
“…Indeed, further studies (Guinee and O'Kennedy, unpublished data) in our laboratory have shown that the levels of water-soluble protein extracted from model PCs made using different levels of disodium orthophosphate anhydrous (0.75-3.4 g¡100 g ) approach 100% of total levels in the cheese, while the levels of soluble calcium increased from 10% to 30% of total Ca, as the ratio of water to PC was increased from 0.5:1 to 10:1 in the preparation of the WSE. A similar observation was made by Shirashoji et al [37] who reported an increase in soluble Ca from 26% to 63% of total calcium as the extraction ratio of cheese-to-water was increased from 1:1 to 1:4 on using tetra sodium pyrophosphate at 0.25 g¡100 g −1 as emulsifying salt.…”
supporting
confidence: 84%
“…Indeed, further studies (Guinee and O'Kennedy, unpublished data) in our laboratory have shown that the levels of water-soluble protein extracted from model PCs made using different levels of disodium orthophosphate anhydrous (0.75-3.4 g¡100 g ) approach 100% of total levels in the cheese, while the levels of soluble calcium increased from 10% to 30% of total Ca, as the ratio of water to PC was increased from 0.5:1 to 10:1 in the preparation of the WSE. A similar observation was made by Shirashoji et al [37] who reported an increase in soluble Ca from 26% to 63% of total calcium as the extraction ratio of cheese-to-water was increased from 1:1 to 1:4 on using tetra sodium pyrophosphate at 0.25 g¡100 g −1 as emulsifying salt.…”
supporting
confidence: 84%
“…The combined action of proteolysis by residual coagulant and reduction in calcium content has been shown to improve meltability of Mozzarella cheeses (Fife et al 1996). It has also been observed that TSC chelated Ca from colloidal calcium phosphate and dispersed casein; the citrateCa complex remained trapped within the process cheese matrix (Shirashoji et al 2006). Swenson et al (2000) observed that use of TSC in fat-free cheese spreads produced properties closest to those of a full-fat reference cheese and provided high meltability.…”
Section: Effect On Physical Properties Of Processed Cheesementioning
confidence: 99%
“…Processed cheese is not a preserved food, but a 'semi-preserved food' with limited shelf life of 3-4 months, especially when the product is packaged in plastic foils, while products stored in metal cans may have longer shelf lives of 6-12 months at room temperature [5]. Chemical composition of processed cheese as reported by many investigators was as following: protein 12.82-22.6, moisture 38.2-64.21%, ash 1.33-4.82, titratable acidity 1.33-1.60 and pH 4.4-6.3 depending on the ingredients used in the manufacture of cheese [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%